The Perspectives of Academicians and Students Regarding the Use of Generative Artificial Intelligence in Higher Education - Torun, Fulya; Sanal, Seda Ozer (Int Soc Technology Education & Science-Istes, 2025)
Education should strive to keep pace with the developments of the modern world and to fulfill its mission by not deviating from the principles of ethical and effective learning. In this process, it continues to be tested by unstoppable technological developments. GAI, with both its positive and negative effects, has spread incredibly quickly to every aspect of our lives. This study, which deals with GAI especially in the context of higher education, aims to evaluate the benefits and limitations of GAI on a common ground. In this context, both academicians and university students were asked to express their views on the current situation regarding the use of AI in higher education and their suggestions for the use of AI in higher education. In the study conducted within the framework of qualitative research, semi-structured interview forms prepared by the researchers were answered by 36 university students and 14 academicians. Academicians and students advocated the need for improvement in the use of GAIs, especially in terms of ease of access to information and teaching/learning support. In addition, it was stated that there are ethical problems in use; they stated that it would be important to take precautions and provide general awareness trainings.
Keywords: Generative artificial; intelligence; Higher education; Interview; Thematic analysis